KUALITAS PELAYANAN ADMINISTRASI KEMAHASISWAAN DI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU - Saputra, Hardiansya; ", Zulkarnaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The growth of university need a good quality in service, aspecially the service by the faculty itself. A faculty has importants role in the university such as, to fullfit the expectation of the candidate of the students, the students limited access about the scholarship and something like that. In the fact, one of duties of the students subgroup is to prapare about the scholarship it self. Based on the promblem above, the researcher interested to know do the research about how the quality of students adminstration service in the facuality of social and politic at university of riau.The theory of cancept that used by the researcher was agus dwiyanto, there are some dimensions of the quality of students administration service, such as: the service of administration, the prosedure, time, facilities, and the resuait of service itself.This recearch used descriptive method that used qualitative result that got by interview some informan and analysis bye the researcher.The result of this research showed that the quality of students administration service in the faculty of social and politic was good enaugh. In the other hand, it still has some weakness in the qualty of service itself.Key words: quality, service, students administration